The Social Services : The immediate problem and the way forward (London : The Socialist Medical Assocation)
1944 1944 1940s 34 pages nurseries. These are too often regarded as a temporary war-time necessity, to assist war industry and to be done away with as soon as possible. But the workers in nurseries, and many mothers, have learnt that the nursery offers the young mother, whether she works or not, freedom from the drudgery and loneliness of a life centred round the kitchen and the baby, and have given the child an opportunity for social and physical development which even the best home cannot provide. Nurseries must not be closed after the war, but developed both now and in the post-war period to become centres of education for young girls, and for parents, who should be encouraged to take a larger part in the running of nurseries. They might well be part of any community centre, and they should not be restricted as at present to children of working women, but open to all. A new development which is needed at once is that of residential nurseries for use during the illness or holidays of parents, and when times become better nurseries at places such as railway stations and shops will be needed, so that women can have a day's shopping or recreation without the fatigue and anxiety of dragging the children round with them, or leaving them at home alone. 2. Children. Evacuation, the first social disturbance of the 5 15X/2/464/1